The Effectiveness of Virtual Museums in Enhancing Student Interest in History Learning - Shalgimbekov, Aibek; Nauryzbayeva, Elmira; Gallyamova, Zemfira (Journal of Education Culture and Society, 2025)
Aim. The objective of this study is to assess the effectiveness of utilizing virtual museums in the context of students’ study of history.Methods. To achieve this goal, a survey was conducted among history students from leading universities in Kazakhstan, such as Al-Farabi Kazakh National University, A. Baitursynov Kostanay Regional University, and L. N. Gumilyov Eurasian National University. The article also shows the educational potential of the virtual archaeological museum of the Kazan Federal University, which allows for a more detailed study of the early period of the Middle Volga region.Results and conclusions. As a result of the research, 82% of students noted that virtual museums provide sufficient information for successful history learning. Regarding student engagement in the learning process using virtual museums, an average score of 7.4 out of 10 was recorded, indicating a high level of student interest in applying this teaching method. Furthermore, 91% of respondents believe that virtual museums contribute to a more captivating study of history, emphasising the importance of utilizing technology to create engaging educational environments.